Design And Simulation Of High Q Inductors On Au-Compensated High Resistivity Silicon - Yap, Chee Seong (Universiti Sains Malaysia, 2017)
The potential of the Au-compensated high resistivity silicon as a microwave substrate was investigated as the high resistivity semiconductor substrates play a crucial role in low loss and high performance MMIC devices. High resistivity substrates are essential to keep the signal-to-noise ratio at acceptable levels and provide high power transmission efficiency in microwave application. The Au-compensated high resistivity can be used as a base substrate which able to be incorporated into the RF-MMIC technology such as integration of IPDs, TSVs and buried oxide. The integration of the IPD was the concern in this work and the meander inductor was chosen as the passive device due to its truly planar characteristic. In this work, three meander inductors with different number of segments of the greatest length was designed and simulated by using the Au-compensated high resistivity substrate. In addition, the inductance for the meander inductors was calculated and the calculation was based on Greenhouse 1974 and Grover 1954. Based on the simulation result, the Q factor of the meander inductor decreases as the number of segments of the greatest length increases. Besides, the Q factor of the meander inductor increases as its inductance decreases which means there is a trade-off between the Q factor of the meander inductor and its inductance value.